Accesibilidad para ingresar a la Educación Superior: desafíos y logros desde el enfoque de la diversidad - Chiny Naranjo, Jeannette (2008)
Concerning the social role, humanistic mission, professional training and development of knowledge pursued by state universities, this article poses the challenge of valuing the difference and acknowledging diversity as a true commitment to society. From the standpoint of diversity, the article proposes to embrace the population with disabilities from the time of entrance and admission to Universidad Nacional.